A ureteral mass presenting as deep vein thrombosis: A very rare presentation - Sharma, Dushiant; Sharma, Umesh; Sood, Rajeev (Indian Journal of Case Reports, 2019)
Deep Vein Thrombosis (DVT) is a dreaded condition, caused by an interplay of a triad of factors consisting ofhypercoagulability, vascular endothelial dysfunction, and stasis. Stasiscan lead tothe development of DVT due to mass external compression over pelvic veins. Here, we present the case of a 45-year-old female who presented with sudden onset left lower limb swelling who was diagnosed to have left iliac venous thrombosis caused by external compression due to an advanced ureteric malignancyunderlining the need for a thorough evaluation in such patients to reveal a more sinister pathology.